Measuring material deprivation with EU-SILC: Lessons from the irish survey - Christopher T. Whelan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2005)
In this paper we consider the consequences for measurement of material deprivation, consistent poverty and economic vulnerability of the shift from the ECHP data set to the EU-SILC instrument. Despite the restricted number of deprivation items available in EU-SILC, we show that there is a substantial overlap between such measures when they are estimated using EU-wide and Irish specific indicators. By placing the EU-wide measures in the context of the full range of Irish indicators, we demonstrate that they allow us to identify clusters of individuals sharply differentiated in terms of their multidimensional deprivation profiles. They also provide an understanding of the socio-economic factors associated with such differentiation that departs in only modest respects from that derived from the more comprehensive set of Irish specific indicators.
Keywords: 330; income poverty; material deprivation; multidimensionality; consistent poverty; economic strain; economic stress